Recent Progress in Understanding the Impact of Food Processing and Storage on the Structure–Activity Relationship of Fucoxanthin - Gomez Zavaglia, Andrea (2023)
Fucoxanthin, a brown algae carotenoid, has attracted great interest because of its numerous biological activities supported by in vitro and in vivo studies. However, its chemical structure is susceptible to alterations when subjected to food processing and storage conditions, such as heat, oxygen, light, and pH changes. Consequently, these conditions lead to the formation of fucoxanthin derivatives, including cis-isomers, apo-fucoxanthinone, apo-fucoxanthinal, fucoxanthinol, epoxides, and hydroxy compounds, collectively known as degradation products. Currently, little information is available regarding the stability and functionality of these fucoxanthin derivatives resulting from food processing and storage. Therefore, enhancing the understanding of the biological effect of fucoxanthin derivatives is crucial for optimizing the utilization of fucoxanthin in various applications and ensuring its efficacy in potential health benefits. To this aim, this review describes the main chemical reactions affecting the stability of fucoxanthin during food processing and storage, facilitating the identification of the major fucoxanthin derivatives. Moreover, recent advancements in the structure–activity relationship of fucoxanthin derivatives will be critically assessed, emphasizing their biological activity. Overall, this review provides a critical updated understanding of the effects of technological processes on fucoxanthin stability and activity that can be helpful for stakeholders when designing processes for food products containing fucoxanthin.